Pathophysiology of Major Depression by Clinical Stages - de Menezes Galvão, Ana Cecília; Almeida, Raíssa Nobrega; de Sousa, Geovan Menezes; Leocadio-Miguel, Mario André; Palhano-Fontes, Fernanda; de Araujo, Dráulio Barros; Lobão-Soares, Bruno; Maia-de-Oliveira, João Paulo; Nunes, Emerson Arcoverde; Hallak, Jaime Eduardo Cecilio; Schuch, Felipe Barreto; Sarris, Jerome; et al. (Frontiers in Psychology, 2021)
The comprehension of major depression disorder (MDD) pathophysiology is essential to the strengthening of precision psychiatry. In order to determine the relationship between MDD pathophysiology and the clinical disease progression, analyzed by the severity of the depressive symptoms and the sleep quality, we conducted a study assessing different peripheral molecular biomarkers: the levels of plasma C-Reactive Protein (CRP), serum mature Brain-Derived Neurotrophic Factor (mBDNF), serum cortisol (SC), and salivary Cortisol Awakening Response (CAR), of patients with MDD (n= 58) and a control group of healthy volunteers (n= 62). Patients with first episode of MDD (n= 30) had significant higher CAR and SC than the controls (n=32) and a similar mBDNF levels. Patients with treatment-resistant depression (TRD n=28) showed significant lower levels of SC and CAR, and higher levels of mBDNF and CRP, than the controls (n=30). Increased severity of depressive symptoms and worse sleep quality were negatively correlated with SC and CAR, and positively for mBDNF. These results are pointing a strong relationship between the clinic progression of MDD and changes in a range of relevant biological markers. This can assist in the development of precision psychiatry and future researches of biological tests of depression.